Discerning cultural homegenisation: crisis of identity and sense of unbelonging in the kindness of enemies by Leila Aboulela - Azman, Maryam; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2020)
Leila Aboulela, a Sudanese diasporic writer living in Scotland, is a prolific contemporary immigrant Muslim woman writer who has written notable fiction on the lives of female characters, who are also migrant Muslims, and their struggles to adapt to their new host countries. A contemporary novel by Aboulela, namely the historical fiction The kindness ofenemies (2015), revolves around the protagonist, Natasha, and her crisis of identity and sense of unbelonging in Britain. While previous studies on the text have applied the framework of Islamic feminism in relation to the concept of topography (Idris & Zulfiqar, 2017), the concepts of history and cultural memory (Kershaw, 2017), postcolonialism (Almaeen, 2018), and the concept of history (Awad, 2018) in analysing the novel, the issues concerning Natasha’s crisis of identity and sense of unbelonging need to be further examined through the lens of cultural studies due to the gap in scholarship on this aspect of the novel. This study will apply the concept of cultural homogenisation by Stuart Hall (1992) which refers to the reduction of cultural distinctions to a phenomenon of global currency. Thus, the objective of this study is to examine how the author depicts Natasha’s adoption of the Western culture to acquire a sense of belonging in Britain through Hall’s concept of cultural homogenisation. The findings of this study reveal that the phenomenon of cultural homogenisation is present in Natasha’s adoption of the Western culture and also the eroding of her Sudanese and Muslim identities in her quest for a sense of belonging in Britain.